Heat treatment improves the sensory properties of the ultrafiltration by‐product of honeybush (Cyclopia genistoides) extract. (9th August 2021) - Miller, Neil; Petrus, Alicia; Moelich, Erika Ilette; Muller, Magdalena; de Beer, Dalene; van der Rijst, Marieta; Joubert, Elizabeth
Abstract: BACKGROUND: Ultrafiltration of green honeybush ( Cyclopia genistoides ) extract results in a by‐product (retentate). Application of further separation processes for recovery of polyphenols would entail creation of additional waste. Repurposing the retentate as a food flavour ingredient provides an alternative valorization approach. RESULTS: The retentate, suspended in water (270 g L −1 ), was heat‐treated at 80 °C for 2, 4, 8 and 16 h, and at 90 °C for 2, 4, 6 and 8 h to change its sensory profile. The heat‐treated retentate, diluted to beverage strength (2.15 g L −1 ), had prominent 'grape/Muscat‐like' and 'marmalade/citrus' aroma and flavour notes. Overall, heating for ≤ 4 h increased the intensities of positive flavour and aroma notes, while reducing those of 'green/grass', 'hay' and bitterness, whereafter further heating only had a slight effect on the aroma profile at 80 °C ( P  < 0.05), but not at 90 °C ( P  ≥ 0.05). The heat treatments, 80 °C/4 h and 90 °C/4 h, were subsequently applied to different batches of retentate ( n  = 10) to accommodate the effect of natural product variation. Heating at 90 °C produced higher intensities of positive aroma attributes ( P  < 0.05), but was more detrimental to the phenolic stability, compared to 80 °C. CONCLUSION: After heat treatment, the phenolic content of C. genistoides retentate, reconstituted to beverage strength, still fell within the range of a typical 'fermented' (oxidized) honeybush leaf tea infusion. The change in phenolic composition will not diminish the benefit of an improved sensory profile for the retentate by‐product through heating. © 2021 Society of Chemical Industry.